Catalytic aromatization of naphtha under methane environment: Effect of surface acidity and metal modification of HZSM-5. (1st July 2018) - Jarvis, Jack; Wong, Ashley; He, Peng; Li, Qingyin; Song, Hua
Highlights: Aromatization of naphtha under methane is technically feasible. Methane presence favors formation of monoaromatics. Zn and Pt additions to HZSM-5 support facilitate BTX formation. Catalytic performance on aromatization is closely related to its physical properties. Abstract: The reformation of naphtha to obtain valuable chemical intermediates such as BTX has attracted much attention. Here we report a novel catalytic process whereby a bimetallic heterogeneous catalyst in the form of Zn-Pt/HZSM-5 is applied to a flow reactor system to reform a complex naphtha feed under a methane environment. Different levels of acidity of the HZSM-5 support are tested with a superior performance witnessed using a SiO2 :Al2 O3 ratio at 80. Further testing is conducted using Zn as a dehydrogenating component with improved performance witnessed when Zn is loaded to a certain degree. A metal promoter is then combined with Zn to compare the effect of different promoters with superior performance witnessed using Ga and Pt as promoters with Zn. BTX selectivity and BTX yield are reported as 86.44% and 34.22% respectively under the Zn-Pt/HZSM-5 catalyst. External site coverage improves performance for all bimetallic catalysts with the exception of Zn-Pt/HZSM-5, suggesting that Pt might not promote the migration of metal functions to the internal pores during synthesis. XRD spectra demonstrate that Pt addition results in a more intact crystal structure after reaction when compared to Zn alone·NH3 -TPD and DRIFT analyses show a reduced amount of strong acidic sites upon metal loading with an increase in the number of Lewis acid sites and reduced Brönsted sites. This change in acidity could be one of the reasons for an improved performance when Zn-Pt/HZSM-5 is employed. The effect of methane is also witnessed over Zn-Pt/HZSM-5 with improved selectivity, yield (BTX and liquid) and active metal dispersion when compared to a nitrogen environment, suggesting the possible incorporation of methane into the products, BTX in particular. Ultimately, the catalyst employed here opens an avenue for further research into the possible industrial application of naphtha aromatization to form valuable chemical products under methane environment.